Method for manufacturing a composite magnetic film and applications thereof

CN122907506APending Publication Date: 2026-10-13UNIV OF ELECTRONICS SCI & TECH OF CHINA +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611296627.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

本发明针对软磁复合材料在高频应用中存在的涡流损耗高、磁粉与树脂基体界面结合性能不足以及传统固化温度过高难以与PCB及柔性基板工艺兼容的技术难题,提出了一套系统性解决方案

Benefits of technology

1.本发明通过对软磁粉末依次进行退火预处理、硅烷偶联剂低温老化界面改性及TEOS原位水解生成SiO2绝缘包覆层,构建了三层核壳结构。其中,退火处理消除了磁粉内部残余应力,恢复其本征软磁性能;低温老化使硅烷偶联剂在磁粉表面形成稳定有序的自组装界面改性层;TEOS在该改性层上原位水解生成的SiO2绝缘层通过化学键(Si-O-Si)与界面层稳固连接。三者协同作用,既提高了磁粉颗粒间的绝缘性能以降低高频涡流损耗,又通过界面改性层增强了磁粉与树脂基体之间的化学键合,避免了包覆层在使用过程中的剥离脱落,实现了磁性能与界面结合性能的同步优化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907506A_ABST
    Figure CN122907506A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of magnetic composite materials, and provides a preparation method of a composite magnetic film and application thereof; the method first carries out annealing pretreatment on soft magnetic powder to eliminate internal stress, then carries out surface interface modification by using a silane coupling agent and low-temperature aging, further adds tetraethyl orthosilicate to hydrolyze and condense under alkaline conditions, forms a silica insulation coating layer in situ on the surface of the magnetic powder, and obtains magnetic powder with a double-layer structure of an interface modification layer and an insulation coating layer; the obtained magnetic powder is mixed with epoxy resin, active diluent and amine curing agent to prepare a composite magnetic paste, and after coating, the composite magnetic paste is cured at 80-150 DEG C to obtain the composite magnetic film; the method realizes complete curing under mild conditions without high-pressure and high-temperature annealing, and the obtained magnetic film has good interface bonding performance, high-frequency low eddy current loss characteristics and low-temperature process compatibility, and can be applied to PCB planar inductors, integrated inductors and other high-frequency magnetic electronic devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of magnetic composite materials technology, and more specifically, to a method for preparing a composite magnetic film and its application. Background Technology

[0002] With the rapid development of power electronics technology, miniaturized electronic devices, and high-frequency integrated power systems, electronic devices are gradually evolving towards higher frequencies, smaller sizes, and higher integration. Inductors, as key components in power conversion, power management, and signal processing, directly affect the efficiency and stability of electronic systems. Under high-frequency operating conditions, traditional ferrite cores, due to their low permeability, limited saturation flux density, and inability to meet the demands of miniaturization integration, are gradually becoming unsuitable for the development requirements of high-performance integrated inductors.

[0003] Soft magnetic composite materials are functional materials prepared using soft magnetic powder as the magnetic matrix and an insulating medium as the composite phase. They possess high saturation magnetic flux density, tunable magnetic properties, and excellent processing adaptability, making them a key development direction for the core materials of high-frequency inductor cores and possessing broad application prospects in the field of high-frequency integrated electromagnetic devices. However, due to limitations in material structure design and manufacturing processes, this material system still faces several key technical bottlenecks in practical industrial applications, restricting its high-frequency service performance and engineering application value.

[0004] Excessive eddy current loss is the primary problem in high-frequency applications of soft magnetic composite materials. Under high-frequency alternating magnetic field conditions, soft magnetic powder particles are prone to eddy current effects, leading to significant eddy current losses and drastically reducing the operating efficiency of inductor devices. Currently, the mainstream solution in the industry is to coat the magnetic powder surface with inorganic insulating materials such as silica to enhance the insulation barrier between powder particles, thereby suppressing eddy current losses. However, a single inorganic insulating coating system has inherent defects. The interfacial compatibility and bonding performance between the inorganic insulating layer and the resin matrix are poor, easily forming microscopic defects such as pores and microcracks within the composite material, ultimately leading to the attenuation of the material's magnetic properties and a decrease in mechanical stability.

[0005] To improve the interfacial affinity between the two phases and reduce internal defects, existing technologies typically employ coupling agents to modify the surface of soft magnetic powder before inorganic insulation coating, thereby optimizing the interfacial bonding between the magnetic powder and the resin matrix. However, this modification scheme still has significant limitations: the organic modified layer of the coupling agent has poor structural compatibility with the subsequently deposited inorganic insulation layer, and a stable chemical bond cannot be formed between the two layers. This leads to problems such as peeling and detachment of the composite coating layer during material forming and long-term service, resulting in a very limited effect on improving the interfacial bonding strength. Furthermore, traditional coupling agent modification processes often employ high-temperature rapid heating and drying curing, making it difficult to precisely control the forming state of the modified layer. This easily leads to problems such as uneven thickness and insufficient density of the modified layer, further weakening the actual effect of surface modification.

[0006] In addition, poor compatibility of curing processes is a key technological bottleneck limiting its integrated application. Currently, the preparation of soft magnetic composite films generally requires high-temperature curing processes above 200°C. However, these high-temperature conditions are incompatible with the standardized manufacturing processes of flexible substrates, PCB substrates, and integrated inductors, making it impossible to meet the fabrication requirements of high-frequency integrated and flexible electromagnetic devices. This greatly limits the promotion and application of soft magnetic composite materials in the field of high-end high-frequency integrated inductor devices.

[0007] To address the aforementioned issues, some studies have attempted to combine coupling agent modification with inorganic insulating coating in composite surface treatment processes. However, achieving structural matching and synergistic effects between the magnetic powder surface modification layer and the insulating coating layer without significantly increasing process complexity, while also ensuring compatibility with low-temperature curing processes, remains a pressing technical challenge in this field.

[0008] Therefore, developing a composite magnetic film material that combines good interfacial bonding performance, high-frequency low-loss characteristics, and low-temperature curing capability is of great significance for the development of high-frequency integrated inductor devices. Summary of the Invention

[0009] This invention relates to the field of magnetic composite materials and electronic devices, specifically providing a method for preparing composite magnetic films and their applications. This invention addresses the technical challenges of high eddy current losses, insufficient interfacial bonding between magnetic powder and resin matrix, and the incompatibility of traditional high-temperature curing temperatures with PCB and flexible substrate processes in high-frequency applications of soft magnetic composite materials, and proposes a systematic solution.

[0010] First, the soft magnetic powder is pre-treated by annealing to eliminate residual stress inside the powder and restore its intrinsic soft magnetic properties. Then, the surface interface of the magnetic powder is modified by 3-aminopropyltriethoxysilane (APTES), and aged at low temperature to form a stable and ordered self-assembled interface modification layer. Then, tetraethyl orthosilicate (TEOS) is used as the silicon source for hydrolysis and condensation under alkaline conditions to generate a silica insulating coating layer in situ on the surface of the magnetic powder, thus constructing a three-layer core-shell structure magnetic powder of soft magnetic core-APTES interface layer-SiO2 insulating layer. On this basis, the insulating coated magnetic powder is dispersed in a low-temperature curing resin system composed of epoxy resin, butyl glycidyl ether (BGE) reactive diluent and ethylenediamine amine curing agent. After coating and film formation, it is completely cured at 80~150℃ to obtain a composite magnetic film.

[0011] Through the synergistic effect of the above-mentioned annealing pretreatment, low-temperature aging interface modification, TEOS in-situ insulation coating and low-temperature complete curing process, this invention effectively balances the optimization of the soft magnetic properties of the magnetic powder body, the enhancement of the bonding strength of the magnetic powder-resin interface, the suppression of high-frequency eddy current loss between particles, and the compatibility with PCB and flexible substrate processes without the need for high-pressure and high-temperature annealing. The resulting composite magnetic film can be directly used as an end product in PCB planar inductors, integrated inductors and other high-frequency magnetic electronic devices.

[0012] In a first aspect, the present invention provides a method for preparing a composite magnetic film, comprising the following steps: S1: Disperse the magnetic powder in a solvent, add a silane coupling agent for surface modification treatment, and form an interface modification layer on the surface of the magnetic powder; S2: Tetraethyl orthosilicate is added to the surface-modified magnetic powder mixture, and a hydrolysis-condensation reaction is carried out under alkaline conditions to form a silica insulating coating layer on the surface of the magnetic powder particles. After the reaction is completed, the particles are separated and dried to obtain insulating coated magnetic powder. S3: Mix epoxy resin, reactive diluent and solvent evenly to form epoxy resin system, add the insulating coated magnetic powder to the epoxy resin system, stir to make the magnetic powder evenly dispersed, add amine curing agent, continue stirring to obtain composite magnetic slurry; S4: The composite magnetic slurry is coated onto the surface of the substrate and cured to obtain a composite magnetic film.

[0013] In this method, the silane coupling agent forms an organic interface layer with active functional groups (such as amino groups) on the surface of the magnetic powder through a hydrolysis-condensation reaction. On the one hand, the interface layer acts as a molecular bridge to provide uniform anchoring points for the subsequent hydrolysis-condensation of TEOS in S2, so that SiO2 is not directly deposited on the surface of the magnetic powder but grows in situ on the interface layer as a substrate. On the other hand, its terminal functional groups can chemically crosslink with the epoxy resin matrix in S3, thereby establishing a continuous chemical bonding transmission path between the magnetic powder and the resin.

[0014] This invention utilizes the sequential combination of S1 and S2 to first construct an organic anchoring layer, followed by in-situ growth of an inorganic insulating layer. This allows for a stable connection between the organic interface layer and the inorganic SiO2 layer via chemical bonds (Si-O-Si). Simultaneously, the amino groups at the other end of the organic layer undergo ring-opening addition reactions with the epoxy groups in the resin matrix, forming a complete chemical bonding network from the magnetic powder surface to the resin matrix. This fundamentally prevents the coating layer from peeling off during use. The low-temperature reactivity of the reactive diluent and amine curing agent in S3 ensures that the low-temperature curing conditions are sufficient to drive resin crosslinking without damaging the interface layer structure. Thus, under mild conditions without high temperature and high pressure, the entire path performance is optimized from the inside of the magnetic powder to the resin matrix. The intrinsic properties of the magnetic powder are preserved, the interfacial bonding strength is guaranteed, and high-frequency eddy current losses are suppressed.

[0015] Preferably, the magnetic powder in S1 further includes a pretreatment step: dispersing the magnetic powder in a mixed solution of anhydrous ethanol and deionized water, ultrasonically cleaning, filtering and drying, and then annealing to obtain pretreated magnetic powder; the annealing temperature is 200~400℃ and the time is 1~4 h.

[0016] Preferably, after the surface modification treatment described in S1 is completed, the process further includes aging the magnetic powder mixture in an environment of 0~10℃ for 12~48 h.

[0017] Preferably, the silane coupling agent in S1 is selected from one or more of aminosilane, epoxysilane, and methacryloxysilane, and is mixed in any proportion; the mass ratio of the silane coupling agent to the magnetic powder is 0.05~0.2:1.

[0018] Preferably, in S2, the pH value is adjusted to 10-11 by adding ammonia, the mass ratio of tetraethyl orthosilicate to magnetic powder is 0.05-0.2:1, and the hydrolysis-condensation reaction is carried out under the condition of stirring at 40-50°C for 1-4 hours.

[0019] Preferably, the reactive diluent in S3 is butyl glycidyl ether, and the amount added is 10% to 20% of the epoxy resin mass; the amine curing agent is an aliphatic amine curing agent, and the amount added is 5% to 20% of the epoxy resin mass.

[0020] Preferably, the amine curing agent is selected from ethylenediamine, diethylenetriamine, or triethylenetetramine.

[0021] Preferably, the curing temperature in S4 is 80~150℃ and the time is 10~40 min.

[0022] Secondly, the present invention provides a composite magnetic film.

[0023] Thirdly, the present invention provides an application of composite magnetic film in the fabrication of PCB planar inductors, integrated inductors, or high-frequency magnetic electronic devices.

[0024] In summary, the present invention has at least one of the following beneficial technical effects: 1. This invention constructs a three-layer core-shell structure by sequentially subjecting soft magnetic powder to annealing pretreatment, low-temperature aging interface modification with silane coupling agent, and in-situ hydrolysis of TEOS to generate a SiO2 insulating coating layer. Annealing eliminates residual stress within the magnetic powder, restoring its intrinsic soft magnetic properties; low-temperature aging allows the silane coupling agent to form a stable and ordered self-assembled interface modification layer on the magnetic powder surface; the SiO2 insulating layer generated by in-situ hydrolysis of TEOS on this modified layer is firmly connected to the interface layer via chemical bonds (Si-O-Si). The synergistic effect of these three processes not only improves the insulation performance between magnetic powder particles to reduce high-frequency eddy current losses, but also enhances the chemical bonding between the magnetic powder and the resin matrix through the interface modification layer, preventing the coating layer from peeling off during use, thus achieving simultaneous optimization of magnetic properties and interface bonding performance.

[0025] 2. This invention uses BGE as an active diluent in combination with ethylenediamine amine curing agents to construct a low-temperature curing epoxy resin system. Combined with the aforementioned APTES interface layer and SiO2 insulating layer double-layer structure, complete curing can be achieved at 80-150℃, avoiding the damage to the APTES organic interface layer caused by high-temperature curing or annealing, and fully preserving the chemical bonding network on the magnetic powder surface. Compared to existing semi-cured magnetic films that require high-temperature curing exceeding 200℃ or subsequent hot-pressing, the low-temperature complete curing process of this invention not only simplifies the preparation process and reduces energy consumption, but also enables the composite magnetic film to be directly compatible with flexible substrates such as PET film and PCB substrate processes, achieving a ready-to-use end-product form.

[0026] 3. The complete process provided by this invention has interconnected steps, and the entire preparation process does not require harsh conditions such as high pressure and high temperature annealing. It overcomes three major technical challenges at the same time under a mild process environment: high high frequency eddy current loss, weak bonding between magnetic powder and resin interface, and poor adaptability to high temperature processing technology. The resulting composite magnetic film can be directly used in PCB planar inductors, integrated inductors and various high frequency magnetic electronic devices. Attached Figure Description

[0027] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the description of the embodiments of this application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0028] Figure 1A process flow diagram of the composite magnetic film preparation method provided in the embodiments of this application is shown; Figure 2 This paper shows a comparison of scanning electron microscopy (SEM) images of the soft magnetic powder insulating coating treatment before and after the treatment in Embodiment 1 of this application. Figure 2 a is the original magnetic particle SEM image. Figure 2 b is a SEM image of the coated magnetic powder; Figure 3 A comparison diagram of the Fourier transform infrared (FTIR) spectra of the original magnetic powder and the coated magnetic powder in Embodiment 1 of this application is shown; Figure 4 This paper presents a comparison chart of the hysteresis loop (VSM) test results of the original magnetic powder and the coated magnetic powder at room temperature in Example 1 of this application; Figure 5 The diagram shows a comparison of the permeability test results of the original magnetic film and the coated magnetic film in the frequency range of 1 MHz to 100 MHz in Embodiment 1 of this application. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. Based on the embodiments of the present invention, any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the protection scope of the present invention. Furthermore, all other embodiments obtained by those skilled in the art without inventive effort are within the protection scope of the present invention.

[0030] Specific experimental steps or conditions are not specified in the embodiments; they can be performed according to the conventional experimental steps or conditions described in the prior art. Reagents and other instruments used, unless otherwise specified, are all commercially available conventional reagent products. Furthermore, the accompanying drawings are merely illustrative diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the drawings denote the same or similar parts, and therefore, repeated descriptions of them will be omitted. Some block diagrams shown in the drawings are functional entities and do not necessarily correspond to physically or logically independent entities.

[0031] Techniques, methods, and devices known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and devices should be considered part of this specification.

[0032] In the description of this invention, it should be understood that the use of terms such as "first" and "second" to define components is merely for the purpose of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore should not be construed as limiting the scope of protection of this invention.

[0033] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0034] To enable those skilled in the art to better understand this application, the following embodiments will be used to provide a detailed description of a method for preparing a composite magnetic film and its application.

[0035] Example Example 1 This embodiment provides a low-temperature curing, low-loss composite magnetic film for high-frequency inductor devices, and the process flow of its preparation method is as follows: Figure 1 As shown, the specific steps include: (1) Magnetic powder pretreatment 10 g of FeSiCr soft magnetic powder (average particle size approximately 2–5 μm) was weighed and dispersed in a mixed solution of 100 mL anhydrous ethanol and deionized water at a volume ratio of 9:1. The powder was ultrasonically cleaned for 10 min to remove impurities and oil stains adhering to the surface of the magnetic powder. After filtration, the powder was dried in an 80 ℃ forced-air drying oven for 4 h. Subsequently, it was annealed at 300 ℃ for 3 h to eliminate internal residual stress and lattice defects introduced during the powder preparation process, thereby restoring its intrinsic soft magnetic properties (reducing coercivity and increasing saturation magnetization) to obtain pretreated magnetic powder.

[0036] (2) Magnetic powder surface interface modification treatment The pretreated magnetic powder was redispersed in a 9:1 volume ratio of anhydrous ethanol to deionized water in 100 mL. 0.5 mL of APTES (approximately 0.05:1 mass ratio of APTES to magnetic powder) was added, and the mixture was mechanically stirred at 50 °C for 2 h to allow the APTES molecules to fully hydrolyze and chemically bond to the magnetic powder surface via dehydration condensation. The mixture was then aged at 4 °C for 24 h, allowing the APTES molecules to slowly and orderly self-assemble on the magnetic powder surface, forming a stable, uniform, and dense interface modification layer. The silanol groups at one end of this interface modification layer form chemical bonds with the hydroxyl groups on the magnetic powder surface (Si-OM, where M represents a metal atom), while the amino groups at the other end are exposed, serving as reactive sites for subsequent chemical cross-linking with the epoxy resin matrix.

[0037] (3) Magnetic powder insulation coating treatment Ammonia (approximately 1–5 mL) was added to the surface-modified magnetic powder mixture to adjust the pH to 10, providing an alkaline catalytic environment for TEOS hydrolysis and condensation. Then, 0.5 mL of TEOS (TEOS to magnetic powder mass ratio approximately 0.05:1) was added, and the mixture was mechanically stirred at 40 °C for 3 h to allow TEOS to undergo hydrolysis and condensation under alkaline conditions, resulting in the in-situ growth of a SiO2 insulating coating layer on the APTES interface-modified layer substrate. This SiO2 layer is firmly connected to the APTES interface layer through Si-O-Si chemical bonds, forming a double-core-shell structure of the APTES interface-modified layer and the SiO2 insulating layer, effectively improving the insulation performance between magnetic powder particles and reducing high-frequency eddy current losses. After the reaction, the mixture was centrifuged at 5000 r / min for 5 min, then filtered and washed to remove unreacted TEOS and byproducts. Finally, it was dried in an 80 °C oven for 4 h to obtain the insulating-coated magnetic powder.

[0038] (4) Add 1 g of bisphenol A epoxy resin, 1 g of acetone and 0.12 g of BGE to the reaction vessel. BGE is used as an active diluent. The epoxy groups in its molecular structure can participate in the subsequent curing and crosslinking reaction. The amount added is 12% of the mass of epoxy resin. Stir magnetically for 15 min at 40 °C to ensure that the components are fully mixed and uniform to form an epoxy resin system. Then, add the insulating coated magnetic powder obtained in step (3) to the epoxy resin system in batches (the mass ratio of epoxy resin to magnetic powder is about 1:10). Stir mechanically for 60 min at 40 °C to ensure that the magnetic powder is uniformly dispersed in the resin system and to promote the partial evaporation of solvent to control the viscosity of the slurry. After the solvent in the system has partially evaporated, add 0.08 g of ethylenediamine (the amount added is 8% of the mass of epoxy resin) and continue to stir mechanically for 30 min to ensure that the curing agent and epoxy resin are fully mixed and uniform to obtain a uniformly dispersed composite magnetic slurry.

[0039] (5) Composite magnetic film formation and curing The obtained composite magnetic slurry was uniformly coated onto the surface of a PET film, with a film thickness controlled at approximately 200 μm. It was then placed in a forced-air drying oven and cured at 120 °C for 20 min. At this temperature, ethylenediamine (EDA) undergoes a ring-opening addition reaction with the epoxy resin, and BGE, acting as an active diluent, participates in the construction of the crosslinking network. Simultaneously, the amino groups at the ends of the APTES interface-modified layer also react with the epoxy groups, forming a complete chemically bonded network from the magnetic powder surface through the APTES interface layer to the epoxy resin matrix, ultimately yielding a low-temperature curing, low-loss composite magnetic film. Because the curing temperature is lower than the thermal decomposition temperature of the APTES interface layer, this interface layer is completely preserved during the curing process, ensuring stable chemical bonding between the magnetic powder and the resin matrix.

[0040] like Figure 2As shown, the original magnetic powder ( Figure 2 a) The surface is smooth, the particle outline is clear, and there are no obvious attachments; after surface modification and insulation coating treatment ( Figure 2 (b) The surface of the magnetic powder particles becomes rough, forming a uniform, continuous and dense coating layer with a thickness of about 20~50 nm. No obvious bridging or agglomeration was observed between the particles, indicating that the surface modification and insulation coating treatment successfully achieved uniform coating at the single particle level.

[0041] The FTIR spectra of the original magnetic powder and the coated magnetic powder are as follows: Figure 3 As shown, the original magnetic powder has no obvious characteristic absorption peaks in the spectral range; the coated magnetic powder has a peak at 1046 cm⁻¹. -1 851 cm -1 and 446 cm -1 Three new characteristic absorption peaks appeared at the surface, corresponding to the asymmetric stretching vibration, symmetric stretching vibration, and bending vibration of the Si-O-Si bond, respectively. These characteristic absorption peaks did not appear in the original magnetic powder, indicating that a silicon dioxide insulating coating layer was successfully formed on the surface of the magnetic powder.

[0042] like Figure 4 As shown, the saturation magnetization of the original magnetic powder is approximately 152 emu / g, and the coercivity is approximately 8 Oe; the saturation magnetization of the coated magnetic powder is approximately 145 emu / g, a decrease of approximately 4.6%, while the coercivity remains essentially unchanged. The results indicate that the SiO2 insulating coating layer, as a non-magnetic layer, has a certain dilution effect on the magnetization of the magnetic powder. However, due to the thin thickness (20–50 nm) and uniform density of the coating layer, the negative impact on the intrinsic soft magnetic properties of the magnetic powder is extremely limited. The coated magnetic powder still maintains good soft magnetic properties, indicating that the insulating coating treatment does not significantly degrade the magnetic properties of the magnetic powder.

[0043] Figure 5 The results show the permeability of the original magnetic film and the coated magnetic film in the frequency range of 1 MHz to 100 MHz (magnetic powder to resin mass ratio 10:1). Figure 5 It can be seen that the real part (μ′) of the complex permeability of the coated magnetic film maintains good frequency stability (μ′ is approximately 7~9) throughout the entire test frequency range, while the μ′ of the original magnetic film increases significantly with increasing frequency. The imaginary part (μ″) of the complex permeability of the coated magnetic film, i.e., the loss factor, is lower than that of the original magnetic film across the entire frequency band, decreasing from 0.08 of the original magnetic film to 0.02 of the coated magnetic film at 10 MHz. The results indicate that this invention, through a dual-layer structure design of APTES interface modification and TEOS insulating coating of the magnetic powder, effectively reduces high-frequency eddy current losses while maintaining good permeability characteristics. These results demonstrate that the composite magnetic film prepared by this invention has good high-frequency application performance and is suitable for PCB planar inductors, integrated inductors, and other high-frequency magnetic electronic devices.

[0044] Example 2 This embodiment provides a low-temperature curing, low-loss composite magnetic film for high-frequency inductor devices, the preparation method of which includes the following steps.

[0045] (1) Magnetic powder pretreatment 10 g of FeSiCr soft magnetic powder was weighed and dispersed in a mixed solution of 100 mL anhydrous ethanol and deionized water at a volume ratio of 9:1. The powder was ultrasonically cleaned for 10 min to remove impurities and oil stains adhering to the surface of the magnetic powder. After filtration, the powder was dried in an 80 ℃ forced-air drying oven for 4 h. Subsequently, it was annealed at 300 ℃ for 3 h to eliminate residual stress and lattice defects inside the magnetic powder and restore its intrinsic soft magnetic properties, thus obtaining pretreated magnetic powder.

[0046] (2) Magnetic powder surface interface modification treatment The pretreated magnetic powder was redispersed in a 9:1 volume ratio of anhydrous ethanol to deionized water in 100 mL of the mixture. 1 mL of APTES (the mass ratio of APTES to magnetic powder was approximately 0.1:1) was added, and the mixture was mechanically stirred at 50 °C for 2 h to allow APTES molecules to hydrolyze and chemically bond to the magnetic powder surface via dehydration condensation. The mixture was then aged at 4 °C for 24 h to allow APTES molecules to slowly and orderly self-assemble and arrange themselves on the magnetic powder surface, forming a stable, uniform, and dense interface modification layer. Compared to Example 1, this example, by increasing the amount of APTES, introduces a higher grafting density of amino functional groups on the magnetic powder surface, providing denser anchoring sites for the subsequent SiO2 insulating coating layer, and simultaneously providing more reactive sites for chemical crosslinking with the epoxy resin matrix.

[0047] (3) Magnetic powder insulation coating treatment Ammonia was added to the surface-modified magnetic powder mixture to adjust the pH to 10. Then, 0.5 mL of TEOS (TEOS to magnetic powder mass ratio approximately 0.05:1) was added. The mixture was mechanically stirred at 40 °C for 3 h to allow the TEOS to undergo a hydrolysis-condensation reaction under alkaline conditions. This resulted in the in-situ growth of a SiO2 insulating coating layer on the APTES interface-modified layer. This SiO2 layer was firmly connected to the APTES interface layer via Si-O-Si chemical bonds. After the reaction, the mixture was centrifuged at 5000 r / min for 5 min, filtered, washed, and then dried in an 80 °C oven for 4 h to obtain the insulating coated magnetic powder.

[0048] (4) Epoxy resin composite treatment 1 g of bisphenol A epoxy resin, 1 g of acetone, and 0.12 g of BGE (12% of the epoxy resin mass) were added to a reaction vessel and magnetically stirred for 15 min at 40 °C. Then, insulating coated magnetic powder was added in batches to the epoxy resin system (epoxy resin to magnetic powder mass ratio approximately 1:10), and mechanically stirred for 60 min at 40 °C to ensure uniform dispersion of the magnetic powder and promote partial evaporation of the solvent. After partial solvent evaporation, 0.08 g of ethylenediamine (8% of the epoxy resin mass) was added, and mechanical stirring continued for 30 min to obtain the composite magnetic slurry.

[0049] (5) Composite magnetic film formation and curing The obtained composite magnetic slurry was uniformly coated onto the surface of a PET film, with the film thickness controlled at approximately 200 μm. It was then cured in a 120 ℃ forced-air drying oven for 20 min to obtain a low-temperature cured, low-loss composite magnetic film. At this temperature, the amino and epoxy groups at the ends of the APTES interface-modified layer react to form a chemically bonded network extending from the magnetic powder surface through the APTES interface layer to the epoxy resin matrix. This interface layer is completely preserved because the curing temperature is lower than its thermal decomposition temperature.

[0050] Example 3 This embodiment provides a low-temperature curing, low-loss composite magnetic film for high-frequency inductor devices, the preparation method of which includes the following steps.

[0051] (1) Magnetic powder pretreatment 10 g of FeSiCr soft magnetic powder was weighed and dispersed in a mixed solution of 100 mL anhydrous ethanol and deionized water at a volume ratio of 9:1. The powder was ultrasonically cleaned for 10 min to remove impurities and oil stains adhering to the surface of the magnetic powder. After filtration, the powder was dried in an 80 ℃ forced-air drying oven for 4 h. Subsequently, it was annealed at 300 ℃ for 3 h to eliminate residual stress and lattice defects inside the magnetic powder and restore its intrinsic soft magnetic properties, thus obtaining pretreated magnetic powder.

[0052] (2) Magnetic powder surface interface modification treatment The pretreated magnetic powder was redispersed in a mixed solution of 100 mL anhydrous ethanol and deionized water at a volume ratio of 9:1. 0.5 mL of APTES (the mass ratio of APTES to magnetic powder was approximately 0.05:1) was added, and the mixture was mechanically stirred at 50 °C for 2 h to allow APTES molecules to hydrolyze and chemically bond to the magnetic powder surface via dehydration condensation. The mixture was then aged at 4 °C for 24 h to allow APTES molecules to slowly and orderly self-assemble and arrange themselves on the magnetic powder surface, forming a stable, uniform, and dense interface modification layer.

[0053] (3) Magnetic powder insulation coating treatment Ammonia was added to the magnetic powder mixture after surface interface modification to adjust the pH to 10. Then, 1 mL of TEOS (TEOS to magnetic powder mass ratio approximately 0.1:1) was added, and the mixture was mechanically stirred at 40 °C for 3 h to allow the TEOS to undergo a hydrolysis-condensation reaction under alkaline conditions. This resulted in the in-situ growth of a SiO2 insulating coating layer using the APTES interface-modified layer as a substrate. This SiO2 layer was firmly connected to the APTES interface layer via Si-O-Si chemical bonds. Compared to Example 1, this example increased the amount of TEOS (from 0.5 mL to 1 mL), further increasing the thickness of the SiO2 coating layer, which is beneficial for further improving the insulation performance between magnetic powder particles. After the reaction, the mixture was centrifuged at 5000 r / min for 5 min, filtered, washed, and then dried in an 80 °C forced-air drying oven for 4 h to obtain the insulating coated magnetic powder.

[0054] (4) Epoxy resin composite treatment 1 g of bisphenol A epoxy resin, 1 g of acetone, and 0.12 g of BGE (12% of the epoxy resin mass) were added to a reaction vessel and magnetically stirred for 15 min at 40 °C. Then, insulating coated magnetic powder was added in batches to the epoxy resin system (epoxy resin to magnetic powder mass ratio approximately 1:10), and mechanically stirred for 60 min at 40 °C to ensure uniform dispersion of the magnetic powder and promote partial evaporation of the solvent. After partial solvent evaporation, 0.08 g of ethylenediamine (8% of the epoxy resin mass) was added, and mechanical stirring continued for 30 min to obtain the composite magnetic slurry.

[0055] (5) Composite magnetic film formation and curing The obtained composite magnetic slurry was uniformly coated onto the surface of a PET film, with the film thickness controlled at approximately 200 μm. It was then cured in a 120 ℃ forced-air drying oven for 20 min to obtain a low-temperature cured, low-loss composite magnetic film. At this temperature, the amino and epoxy groups at the ends of the APTES interface-modified layer react to form a chemically bonded network extending from the magnetic powder surface through the APTES interface layer to the epoxy resin matrix. This interface layer is completely preserved because the curing temperature is lower than its thermal decomposition temperature.

[0056] The composite magnetic film prepared in this embodiment was tested by SEM, FTIR, VSM and permeability, and the results were basically consistent with those of Example 1: a uniform, continuous and dense SiO2 coating layer was formed on the surface of the magnetic powder; characteristic absorption peaks of Si-O-Si bonds appeared in the FTIR spectrum; the coated magnetic powder still maintained good soft magnetic properties; the coated magnetic film had stable permeability and significantly reduced loss factor in the frequency range of 1~100 MHz.

[0057] The results of Examples 1 to 3 show that within the range of APTES dosage of 0.5~1.0 mL / 10g magnetic powder and TEOS dosage of 0.5~1.0 mL / 10g magnetic powder, the technical solution of the present invention can stably achieve good high-frequency and low-loss characteristics, verifying the adjustability of process parameters and the universality of the technical solution.

[0058] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0059] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.

[0060] Finally, it should be noted that in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or terminal device that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or terminal device. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or terminal device that includes said element.

[0061] The preparation method of the composite magnetic film provided in this application and its application have been described in detail above. Specific examples have been used to illustrate the principle and implementation of this application. The description of the above embodiments is only for the purpose of helping to understand the method and core idea of ​​this application. At the same time, for those skilled in the art, there will be changes in the specific implementation and application scope based on the idea of ​​this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A method for preparing a composite magnetic film, characterized in that, Includes the following steps: S1: Disperse the magnetic powder in a solvent, add a silane coupling agent for surface modification treatment, and form an interface modification layer on the surface of the magnetic powder; S2: Tetraethyl orthosilicate is added to the surface-modified magnetic powder mixture, and a hydrolysis-condensation reaction is carried out under alkaline conditions to form a silica insulating coating layer on the surface of the magnetic powder particles. After the reaction is completed, the particles are separated and dried to obtain insulating coated magnetic powder. S3: Mix epoxy resin, reactive diluent and solvent evenly to form epoxy resin system, add the insulating coated magnetic powder to the epoxy resin system, stir to make the magnetic powder evenly dispersed, add amine curing agent, continue stirring to obtain composite magnetic slurry; S4: The composite magnetic slurry is coated onto the surface of the substrate and cured to obtain a composite magnetic film.

2. The method for preparing a composite magnetic film according to claim 1, characterized in that, The magnetic powder described in S1 further includes a pretreatment step: dispersing the magnetic powder in a mixed solution of anhydrous ethanol and deionized water, ultrasonically cleaning, filtering and drying, and then annealing to obtain the pretreated magnetic powder; the annealing temperature is 200~400℃ and the time is 1~4 h.

3. The method for preparing a composite magnetic film according to claim 1, characterized in that, After the surface modification treatment described in S1 is completed, the process also includes aging the magnetic powder mixture in an environment of 0~10℃ for 12~48 h.

4. The method for preparing a composite magnetic film according to claim 1, characterized in that, The silane coupling agent in S1 is selected from one or more of aminosilane, epoxysilane, and methacryloxysilane, and is mixed in any proportion; the mass ratio of the silane coupling agent is 0.05~0.2:

1.

5. The method for preparing a composite magnetic film according to claim 1, characterized in that, In S2, the pH value is adjusted to 10-11 by adding ammonia. The mass ratio of tetraethyl orthosilicate to magnetic powder is 0.05-0.2:

1. The hydrolysis-condensation reaction is carried out under the condition of stirring at 40-50℃ for 1-4 hours.

6. The method for preparing a composite magnetic film according to claim 1, characterized in that, The reactive diluent in S3 is butyl glycidyl ether, and the amount added is 10% to 20% of the epoxy resin mass; the amine curing agent is an aliphatic amine curing agent, and the amount added is 5% to 20% of the epoxy resin mass.

7. The method for preparing a composite magnetic film according to claim 6, characterized in that, The amine curing agent is selected from one of ethylenediamine, diethylenetriamine, or triethylenetetramine.

8. The method for preparing a composite magnetic film according to claim 1, characterized in that, The curing process described in S4 is performed at a temperature of 80~150℃ for a time of 10~40 min.

9. The composite magnetic film prepared by the method of any one of claims 1 to 8.

10. The application of the composite magnetic film as described in claim 9 in the fabrication of PCB planar inductors, integrated inductors, or high-frequency magnetic electronic devices.